Impact of Headache and Over-the-Counter Treatment on Pain and Functional and Cognitive Parameters: A Real-World Study across Three Geographies - Peter J. Goadsby; Andreas Straube; Mamoru Shibata; Mario Fernando Prieto Peres; Caroline Amand; Chris Colby; Mary Kay Margolis; Valentine Polivka; Andrew Stewart; Luminita Constantin (Pain and Therapy)
Abstract Introduction Individuals with headache choose over-the-counter (OTC) medications to relieve pain and associated symptoms. This real-world evidence study investigated the effect of three OTC headache treatments on headache intensity and the associated impairment of cognitive and functional parameters in headache sufferers in Germany, Brazil, and Japan. Methods This prospective, multinational, observational eDiary-based study included adults experiencing headache for ≥ 6 months, with ≥ 2 headache episodes per month requiring treatment and using one of the three OTC headache treatments (Germany: ibuprofen 400 mg + caffeine 100 mg; Brazil: dipyrone 1 g; Japan: ibuprofen 100 mg + caffeine 40 mg). The primary endpoint was change in headache intensity (11-point numeric rating scale [NRS]) from baseline (headache onset) to 2 h post-treatment. Secondary endpoints were association between NRS scores for headache intensity and for cognitive and functional parameters and change in these parameters from baseline to 2 h post-treatment. Results Of the 32,623 individuals screened, 1239 were enrolled in the study, with 607 having their first headache episode treated using one of the OTC treatments. Baseline demographics and characteristics were similar across the cohorts. At 2 h post-treatment, headache intensity significantly improved, with the mean change from baseline being 3.4 (3.1, 3.7, 95% confidence interval), 4.2 (3.9, 4.5), and 3.0 (2.7, 3.3) for German, Brazilian, and Japanese cohorts, respectively. Improvement was observed in all cognitive and functional parameters. The NRS score for headache intensity significantly predicted NRS scores of all cognitive and functional parameters (P < 0.0001). Conclusions The study shows that headache intensity significantly affects cognitive and functional aspects, as well as overall quality of life, for sufferers globally. It confirms the effectiveness of OTC medications and suggests using headache intensity as a self-assessment tool for symptom severity, highlighting the need for new parameters in the OTC domain to improve public health benefits.